Pengaruh Modul Elektronik Ekosistem dan Pencemaran Air terhadap Sikap Lingkungan dan Kemampuan Kognitif Siswa - Rina Wahyuningsih; Dwi Listyorini; Ibrohim Ibrohim (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study aims to determine the effectiveness of the ecosystem and water pollution electronic modules on student’s environmental attitudes and cognitive abilities. This study is a quasi-experimental study with a nonrandomized pretest-posttest control group design. The results of unpaired t-test analysis showed that there was no difference in environmental attitude in the group using the electronic module and textbook with a p-value of 0.955 > α (0.05) and there was a difference in cognitive abilities in the group that used electronic modules and textbooks with a value of p-value (0.012) < α (0.05).Abstrak: Tujuan penelitian untuk mengetahui keefektifan modul elektronik ekosistem dan pencemaran air terhadap sikap lingkungan dan kemampuan kognitif siswa. Penelitian ini merupakan quasi-experimental study dengan desain nonrandomized pretest-posttest control group design. Hasil analisis uji-t tidak berpasangan menunjukkan bahwa tidak terdapat perbedaan sikap lingkungan pada kelas yang menggunakan modul elektronik dan buku teks dengan nilai p value 0,955 > α (0,05) dan terdapat perbedaan kemampuan kognitif pada kelas yang menggunakan modul elektronik dan buku teks dengan nilai p value (0,012) < α (0,05).